Climate change and Singapore - Lee, Kay Li (2012)
The Northern Sea Route (NSR), located in the Arctic, is a shipping route linking the Pacific and Atlantic Ocean. The heightened focus on the Arctic of late is primarily due to the impacts of climate change and the fact that these changes are occurring at an unprecedented rate in this region. Presently, ships can pass the NSR two to three months a year. With the thawing of the Arctic ice, not only will the NSR be passable for longer periods of time, Arctic offshore resources will be more accessible as well. The objectives of this research project aims to investigate the potential impacts on Singapore as a major Hub; and to identify business opportunities for Singapore and the local maritime industries. This research report concentrated on two work packages: the Arctic region to find out the main driving force in the development of NSR, and an overview of Russia to find out the conduciveness of the business environment for foreign investments. A general research was performed to gain an overall understanding of the undertaking before raising research questions and propositions relevant to the issues of each work package for verification. Findings and results revealed that the NSR will not threaten Singapore’s position as a maritime hub. Firstly, the abundance of Arctic oil and gas reserves, not distance savings, is the main driver in the development of the NSR. Secondly, Russia is deemed unfavourable for investments today and in the next fifty years. However, the Arctic offers opportunities for Singapore. Six strategy propositions on how local maritime industries could enter the Arctic market and for Singapore to further establish her position as a maritime hub were discussed.